2020
DOI: 10.2147/ijn.s263797
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anticancer Activity of Thymoquinone Cubic Phase Nanoparticles Against Human Breast Cancer: Formulation, Cytotoxicity and Subcellular Localization</p>

Abstract: Introduction: Triple negative breast cancer is an aggressive disorder which accounts for at least 15% of breast cancer diagnosis and a high percentage of breast cancer morbidity, hence intensive research efforts are focused on the development of effective therapies to overcome the disease. Thymoquinone (TQ), the bioactive constituent of Nigella sativa, exhibits anticancer activity, yet its translation to the clinic is hindered by its poor bioavailability and lack of quantification method in blood and tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 63 publications
6
19
0
Order By: Relevance
“…Furthermore, encapsulating TQ in cubosomal nanoparticles can enhance its antitumor activity by improving the efficient delivery of this compound to target tissues. [136] Consistent with our findings, TQ was also found to exhibit antiproliferative and apoptotic activities in different types of cancer cells via blocking STAT3 activation. This attenuated the transcription and translation of STAT3-regulated targets such as survivin and cyclin D1, inducing G1 phase arrest and caspase-3,7,9 activation.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, encapsulating TQ in cubosomal nanoparticles can enhance its antitumor activity by improving the efficient delivery of this compound to target tissues. [136] Consistent with our findings, TQ was also found to exhibit antiproliferative and apoptotic activities in different types of cancer cells via blocking STAT3 activation. This attenuated the transcription and translation of STAT3-regulated targets such as survivin and cyclin D1, inducing G1 phase arrest and caspase-3,7,9 activation.…”
Section: Discussionsupporting
confidence: 91%
“…TQ, either free, encapsulated in a nanocarrier or in combination with other chemotherapeutics, is very promising against many cancers including cancer stem cells. [39][40][41] Moreover, the results also conrmed the low toxicity of CB [7] that supports the use of CB [7] as a drug carrier. Previously described reports about toxicity and safety of CB[n] demonstrated the relative safety and acceptable toxicity in vitro and in vivo.42,43 For example, Oun et al reported the lack of signicant tissue specic toxicity of CB [6] and CB [7] using ex Fig.…”
Section: Cytotoxicitysupporting
confidence: 61%
“…The synergistic potential of TQ loaded in cockle-shell-derived aragonite CaCl 3 -NPs was reported with doxorubicin to reduce cellular migration in mammary gland carcinoma stem cells (MDA MB 231) [ 186 ]. A cubosomal formulation of TQ improved cellular accumulation, which leads to increased apoptotic activity migration in mammary gland carcinoma cell lines (MDA-MB-231 and MCF-7) [ 187 ]. Chitosan-coated TQ-PLGA-NPs accumulated in melanoma cancer cells (A375) by taking advantage of the EPR effect and positive surface charge of chitosan, which facilitate binding with the negatively charged cell membrane and induce cellular retention as well as time-dependent cytotoxicity [ 188 ].…”
Section: Neoplasm and Its Pathogenesismentioning
confidence: 99%